Impaired Executive Function and Depression as Independent Risk Factors for Reported Delirium Symptoms: An Observational Cohort Study Over 8 Years - Mychajliw, Christian; Herrmann, Matthias L.; Suenkel, Ulrike; Brand, Katharina; von Thaler, Anna-Katharina; Wurster, Isabel; Yilmaz, Rezzak; Eschweiler, Gerhard W.; Metzger, Florian G. (Frontiers in Aging Neuroscience, 2021)
Background Acute medical illnesses, surgical interventions, or admissions to hospital in older individuals are frequently associated with a delirium. In this cohort study, we investigated the impact of specific cognitive domains and depression before the occurrence of delirium symptoms in an 8-year observation of older non-hospitalized individuals. Methods In total, we included 807 participants (48–83 years). Deficits in specific cognitive domains were measured using the CERAD test battery, and depressive symptoms were measured using Beck Depression Inventory and the Geriatric Depression Scale (GDS) before the onset of a delirium. Delirium symptoms were retrospectively assessed by a questionnaire based on the established Nursing Delirium Screening Scale. Results Fifty-eight of eight hundred seven participants (7.2%) reported delirium symptoms over the 8-year course of the study. Sixty-nine percent (n = 40) of reported delirium symptoms were related to surgeries. In multivariate regression analysis, impaired executive function was an independent risk factor (p = 0.034) for the occurrence of delirium symptoms. Furthermore, age (p = 0.014), comorbidities [captured by the Charlson Comorbidity Index (CCI)] (p < 0.001), and depression (p = 0.012) were significantly associated with reported delirium symptoms. Conclusion Especially prior to elective surgery or medical interventions, screening for impaired executive function and depression could be helpful to identify patients who are at risk to develop delirium symptoms.